PEMBANGUNAN EKONOMI DAN LINGKUNGAN BERKELANJUTAN BERBASIS REFORMA AGRARIA DI BEBERAPA NEGARA DAN INDONESIA KEKINIAN - Virtuous Setyaka (UIR PRESS, 2016)
This paper intends to discuss the theoretical discourse and practice of Agrarian Reform in various countries of the world. By exploring the concepts and theories of Agrarian Reform, Economic Development and Sustainable Environment and practices in various countries through literature studies, it is expected to contribute as an elaboration which may be important as a comparison in the implementation of sustainable development in Indonesia especially in the implementation of Agrarian Reform for economic welfare, Environmental sustainability, and minimization of social conflict of kekininian.